2010
DOI: 10.1542/peds.2009-1510
|View full text |Cite
|
Sign up to set email alerts
|

Defining the Reference Range for Oxygen Saturation for Infants After Birth

Abstract: These data represent reference ranges for Spo(2) in the first 10 minutes after birth for preterm and term infants.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

21
397
4
28

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 504 publications
(450 citation statements)
references
References 27 publications
21
397
4
28
Order By: Relevance
“…We found that it took 7.4 minutes to reach a median pre- [10][11][12][13]. Our study supports the assertion that during neonatal transition oxyhemoglobin saturation does not reach 90% until approximately 10 minutes of life.…”
Section: Discussionsupporting
confidence: 88%
See 3 more Smart Citations
“…We found that it took 7.4 minutes to reach a median pre- [10][11][12][13]. Our study supports the assertion that during neonatal transition oxyhemoglobin saturation does not reach 90% until approximately 10 minutes of life.…”
Section: Discussionsupporting
confidence: 88%
“…There have been similar studies both in the past and more recently, having smaller and even larger numbers of infants, from centres across all continents [10][11][12][13][14][15][16]. Kamlin et al determined the range of only pre-ductal SpO 2 in 92 patients who were found to have a median SpO 2 of 90% at 5 minutes [12].…”
Section: Discussionmentioning
confidence: 87%
See 2 more Smart Citations
“…Under these circumstances especially sensitive tissues, such as the retina and choroid are vulnerable towards damage. It is therefore important to define a safety range of postnatal oxygenation that would avoid damage caused by both hyper-and/or-hypoxia in the immediate postnatal period (2), and thereafter (1).…”
mentioning
confidence: 99%